Adsorption of copper, cadmium, lead and zinc onto a synthetic manganese oxide - Della Puppa, Loïc; Komárek, Michael; Bordas, François; Bollinger, Jean-Claude; Joussein, Emmanuel (Journal of colloid and interface science, 2013)
Due to its simple and inexpensive synthesis, a new amorphous hydrous manganese oxide (AMO) has been studied as a possible chemical stabilizing agent for soils contaminated with metals. Preliminary experiments evaluating the stability of AMO in pure water have reported only minor dissolution (5.70% and 0.24% depending on the w/v ratio). Sorption kinetics have shown fast metal adsorption, especially for Pb. The sorption capacities of AMO for Cu, Cd, Pb, and Zn have been described and compared with synthetic birnessite for pH 4 and 5.5. Both oxides show similar sorption capacities at pH 4 despite the fact that birnessite characteristics (pH of zero point charge, specific surface area and cation exchange capacity) are more favorable for metal sorption. Moreover, the pH adsorption-edges show that the AMO is more pH-dependent than birnessite.